Paclitaxel, topotecan, and carboplatin in metastatic endometrial cancinoma: A Hellenic Co-operative Oncology Group (HeCOG) study - Papadimitriou, C.A.; Fountzilas, G.; Bafaloukos, D.; Bozas, G.; Kalofonos, H.; Pectasides, D.; Aravantinos, G.; Bamias, A.; Dimopoulos, M.-A. (Gynecologic Oncology, 2008)
Objective: Taxanes, and platinum compounds represent the chemotherapeutic agents with the greatest activity in metastatic endometrial carcinoma. We administered the combination of paclitaxel, topotecan and carboplatin to patients with metastatic or recurrent carcinoma of the endometrium to evaluate its activity and to define its toxicity. Methods: Thirty-nine consecutive patients were treated on an outpatient basis with paclitaxel 150 mg/m2, administered intravenously over a 3-h period and followed by carboplatin at AUC of 5 on day 3, with both agents proceding topotecan that was given at 0.75 mg/m2/day on days 1 through 3. The chemotherapy was repeated every 3 weeks with granulocyte colony-stimulating factor (G-CSF) support for a maximum of six courses. Results: Twenty-one (60%) patients achieved objective clinical response (95% CI, 42.2-75.7%) including 4 (11.4%) complete and 17 (48.6%) partial responses. The median times to progression and survival for all patients were 8.9 and 17.7 months, respectively. Grade 3 or 4 thombocytopenia and neutropenia occurred in 5 (13%) and 4 (10%) patients, respectively, but only 2 episodes of neutropenic fever were encountered. Grade 2 or 3 neurotoxicity was observed in 23% of patients. Conclusions: The combination of paclitaxel, topotecan and carboplatin with G-CSF support appears active with acceptable toxicity in patients with metastatic or recurrent carcinoma of the endometrium. © 2008 Elsevier Inc.
Keywords: Carboplatin; Epirubicin; Metastatic endometrial cancer; Paclitaxel